(related to Fig 6) - Lilia Kukovska (22683586) (2025)
Phase planes for A) a circuit with strong competition () and B) a circuit with no competition (), when the preferred stimulus of population 1 is present and the laser is off (). The nullcline is shown in blue and the nullcline is shown in orange. For a circuit with strong competition, there are two stable fixed points, where either the rate of population 1 or the rate of population 2 is large. For a circuit with weak competition, there is only one fixed point. C) The difference in selectivity between laser on and laser off conditions for go- (blue) and no-go-preferring (red) populations for ‘Entire’ and ‘Early’ PV cell activation. Competition in the circuit has been increased to , demonstrating that the conclusions were not strongly dependent on precise parameter choices (see also G). Firing rates over time for 15 simulations of go-preferring populations during 50 go trials with either D) no laser stimulation, E) entire laser stimulation, or F) early laser stimulation. In the no laser condition, the activities end up in one of two fixed points. In the early laser stimulation, most activities end up in the same fixed point. G) Phase planes for a circuit with different competition weights varying from 8.0 to 14.0. The nullcline is shown in blue and the nullcline is shown in orange. There are two stable fixed points, where either the rate of population 1 or the rate of population 2 is large. (TIFF)